THE IMPACT OF STRUCTURAL ANALYTIC SYNTHETIC METHOD ON READING SKILLS OF STUDENTS AT KITA NGEMI HIYATI LUBUK BASUNG ELEMENTARY SCHOOL - Sinta Ardila; HurriyatusSa’diyah; Rita Febrianta; Nur Hasnah (Adisam Publisher, 2025)
This research is motivated by the low learning outcomes of students in reading Arabic texts because the methods used by teachers are not able to attract students' interest. Therefore, appropriate educational facilities are needed to train students' skills in reading Arabic texts; one of these means is using the SAS (structural analytical synthetic) method. The aim of this research is to determine the effect of the SAS method on the Arabic reading skills of our elementary school students in Najmi Biological Lubuk Basung. In this study, the researcher used a quantitative method with a nonequivalent control group design. The total population in this study was 32 people, consisting of two classes. The research consisted of 15 people in the experimental group and 17 people in the control group. The data analysis methods used were normality tests, homogeneity tests, and hypothesis tests. It can be concluded that there is a significant influence on student learning outcomes using the SAS method compared to using traditional methods. This is supported by the calculated T test results, which are 2.120, while the T table results are 2.042 at the 5% level, and the 2-tailed sig is 0.042. So the researcher concludes that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.